2022
DOI: 10.3390/land11122284
|View full text |Cite
|
Sign up to set email alerts
|

The Relationship between Habitat Diversity and Tourists’ Visual Preference in Urban Wetland Park

Abstract: The increasing number of visitors to wetland parks has caused varying degrees of impact on wetland life. How to reduce the damage to wetland biodiversity caused by recreational activities in parks, improve tourists’ recreational experience, and balance the relationship between the two are urgent problems that need to be solved. Therefore, four urban wetland parks were selected as subjects for this study. The present study utilized social media data to study the diversity of urban wetland habitats and tourists’… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
0
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 68 publications
0
0
0
Order By: Relevance
“…Furthermore, the rational utilization of resources can improve the income of local surrounding communities and increase funding sources for wetland protection [27,28]. Such rational utilization can also change the ideological concepts of a community and encourage people to protect wetlands [29] spontaneously.…”
Section: Wetland Parks Are Necessary For the Protection Of Wetland Ec...mentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, the rational utilization of resources can improve the income of local surrounding communities and increase funding sources for wetland protection [27,28]. Such rational utilization can also change the ideological concepts of a community and encourage people to protect wetlands [29] spontaneously.…”
Section: Wetland Parks Are Necessary For the Protection Of Wetland Ec...mentioning
confidence: 99%
“…First, from the perspective of landscape science, research mainly involves the current development and restoration of wetland parks [38], planning and design [35], plant configuration design [34], et cetera. Second, the sociological perspective includes research on wetland value [37], wetland healthcare [3], and the ecological education function of wetland parks [29]. Mitsch, Zhang, Griffiths, and Bays [17] reported that these parks serve as natural laboratories for studying biodiversity and ecosystem function, promoting scientific research that leads to a deep understanding of wetland ecosystems.…”
Section: Wetland Park Research Is Increasing In International Academiamentioning
confidence: 99%
See 1 more Smart Citation